Global commodity chains: cases of turkish textile and apparel industry - Özbay, Zühal (My University, 2007)
Küresel meta ağı analizi küresel ekonomik faaliyetlerdeki yeni iş bölümünü ve var olan meta zincirlerindeki yönetsel yapıları anlamamızı sağlar. Bu bağlamda, bu çalışmada Türkiye deki tekstil ve hazır giyim sektörünü analiz etmeye çalıştım. Bu endüstrilerde deki güç ve otorite ilişkileri alıcı güdümlü meta zincirlerine örnek oluşturur ve bu tip zincirlerde gerçek kar pazarlama, tasarım ve perakendecilik faaliyetleri sonucunda oluşur. Türkiye’nin küresel hazır giyim ve tekstil zincirlerinde rolü, daha ziyade fasona dayalı tam hazırlanmış üretim modeline uygundur. Bu çalışmada, Türkiye deki hazır giyim ve tekstil endüstrisi için bir teknolojik terfi yolu olup olmadığını ve bu yolda Türkiye’nin karşınsında olan uluslararası engelleri, kotaların kalkması, sorunsallarını göstermeye çalıştım. Mavi Jeans firması bu teknolojik terfi gerçekleştirdiği ve fason üretimden marka üretimine geçmeyi başardığı için örnek çalışma olarak seçilmiştir.

Global commodity chain analysis provides a better understanding of a new division of labor in global economic activities and governance structures of existing commodity chains. In this study, I try to analyze Turkish apparel and textile industries which exemplify best labor intensive industries within this context. The power and authority relations in these industries reflect buyer-driven commodity chains in which real rent derives from marketing, design and retailing activities. The role of Turkey in global and apparel commodity chain is rather Original Equipment Manufacturer basis. I show if there is a way to upgrade in to higher level OBM, and I also analyze some international challenges, abolition of quotas, against upgrading process of these industries in Turkey. The company Mavi Jeans as jeans manufacturer which has succeeded in moving into original branded manufacturer is chosen as a case study.
Keywords: Ekonomi; Marka; Tekstil_Ekonomi